Myxoid Spindle Cell Sarcoma With LMNA-NTRK Fusion: Expanding the Morphologic Spectrum of NTRK-Rearranged Tumors. (August 2020) - So, Yik Ka; Chow, Chit; To, Ka Fai; Chan, John K. C.; Cheuk, W.
Neurotrophic tyrosine receptor kinase ( NTRK )-rearranged spindle cell neoplasm is a recently described soft tissue tumor entity that occurs predominantly in children and young adults. The diagnosis of this tumor is difficult due to the nonspecific and highly variable morphology, yet it is of clinical relevance because of the availability of highly effective TRK inhibitors. In this article, we report the case of a 40-year-old female who presented with a mass in the left calf. Histologic examination revealed a low-grade sarcoma consisting of monomorphic spindle cells accompanied by abundant myxoid stroma, a feature that had not been emphasized in the reported cases of NTRK -rearranged tumors. The tumor cells expressed CD34 and S100 but not SOX10, and they showed positive staining for pan-TRK. Next-generation sequencing showed the presence of LMNA-NTRK1 fusion. The patient developed several episodes of lung metastases that eventually became unresectable. TRK inhibitor was given that led to near-complete resolution of the tumors.